Influencing factors for delay in healthcare-seeking, definitive diagnosis, identification in patients with pulmonary tuberculosis in Minhang District - MA Qiongjin, YAN Huiqin, WU Yunhua, GUO Xu, YANG Lijia, TANG Lihong, YANG Shengyuan (预防医学)
Objective: To investigate the influencing factors for delay in healthcare-seeking, definitive diagnosis and identification in patients with pulmonary tuberculosis (PTB) in Minhang District, Shanghai Municipality, so as to provide the basis for effectively reducing delay in PTB patients. Methods: Data of PTB patients in Minhang District from 2017 to 2022 were collected from the Infectious Disease Reporting Information System of Chinese Disease Prevention and Control Information System. The prevalence rates of delay in healthcare-seeking, definitive diagnosis and identification were analyzed, and factors affecting delay in healthcare-seeking, definitive diagnosis and identification were identified using multivariable logistic regression models. Results: A total of 4 214 PTB patients were reported in Minhang District from 2017 to 2022, including 2 802 males and 1 412 females, with a male-to-female ratio of 1.98∶1. The majority of patients were aged 25 to <45 years (1 664 cases, 39.49%). The prevalence rates of delay in healthcare-seeking, definitive diagnosis and identification were 36.81%, 30.21% and 38.09%, respectively. Delay in healthcare-seeking was associated with the year (2018, OR=0.708; 2019, OR=0.549; 2020, OR=0.670; 2021, OR=0.682), gender (female, OR=1.199), occupation (worker, OR=1.379; housekeeping service/housework/unemployed, OR=1.481), case identification route (symptom-based consultation, OR=11.159), and level of the first-diagnosed hospital (city-level, OR=1.528). Delay in definitive diagnosis was associated with age (45 to <65 years, OR=1.476), occupation (commercial service, OR=0.687; housekeeping service/housework/unemployed, OR=0.672), household registration (non-local, OR=0.820), case identification route (symptom-based consultation, OR=0.616), pathogen test result (negative/not tested, OR=1.903), and the level of the first-diagnosed hospital (city-level, OR=0.311). Delay in identification was associated with the year (2018, OR=0.785; 2019, OR=0.647; 2020, OR=0.790; 2021, OR=0.710), occupation (commercial service, OR=0.687), household registration (non-local, OR=0.848) and level of the first-diagnosed hospital (city-level, OR=0.560). Conclusions: Year, gender, occupation, case identification route and level of the first-diagnosed hospital are influencing factors for delay in healthcare-seeking in PTB patients. Age, occupation, household registration, case identification route, pathogen test result and level of the first-diagnosed hospital are influencing factors for delay in definitive diagnosis. Year, occupation, household registration and level of the first-diagnosed hospital are influencing factors for delay in identification.